Assessment of left ventricular function in patients with diabetic nephropathy using two-dimensional speckle-tracking echocardiography - Zhang, Xiunan; Jiang, Cuiping; Ye, Zhibin; Zhang, Yinjia; Zhang, Xiaoli (Frontiers in Endocrinology, 2025)
ObjectiveTo assess cardiac function using two-dimensional speckle-tracking echocardiography (2D-STI) in diabetic nephropathy (DN) patients and investigate the relationship between albuminuria and early cardiac systolic and diastolic dysfunction, along with associated risk factors based on clinical indicators.MethodsA total of 75 patients with DN, 100 patients with diabetes mellitus (DM), and 37 healthy controls were recruited. Clinical data were collected, and conventional echocardiography as well as 2D-STI were performed on all participants.Results2D-STI findings revealed a significant increased occurrence rate of subclinical left ventricular systolic dysfunction [global longitudinal strain values (GLS) <18%], among diabetic patients compared to healthy controls. Furthermore, the proportion of GLS<18% occurrence was higher in the DN group compared to the DM group (p<0.001) and especially higher in the massive albuminuria group than that in the microalbuminuria group (p<0.001). The results demonstrated that albuminuria, eGFR<60 ml/min/1.73 m2, and total cholesterol were identified as significant risk factors for the development of subclinical left ventricular systolic insufficiency in diabetic patients. However, when considering only patients with DN and adjusting for covariates, it was found that only total cholesterol remained statistically significant (p< 0.05).ConclusionThe higher cholesterol levels in patients with DN are associated with a greater risk of subclinical left ventricular systolic dysfunction reflected by a decrease in GLS assayed with 2D-STI.Critical relevance statementGLS measured by 2D-STI combined with clinical indexes to evaluate and predict subclinical left ventricular systolic function in patients with DM, providing reference for early prevention and treatment of cardiac dysfunction in patients with DN.